2020
DOI: 10.1007/s00784-020-03382-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral analysis for perioperative perfusion monitoring—a clinical feasibility study on free and pedicled flaps

Abstract: Objectives In reconstructive surgery, flap monitoring is crucial for early identification of perfusion problems. Using hyperspectral imaging (HSI), this clinical study aimed to develop a non-invasive, objective approach for perfusion monitoring of free and pedicled flaps. Material and methods HSI of 22 free (FF) and 8 pedicled flaps (PF) in 30 patients was recorded over time. Parameters assessed were tissue oxygenation/superficial perfusion (0–1 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 27 publications
2
67
0
Order By: Relevance
“…Recent data on skin HSI monitoring in septic patients points to an association with organ dysfunction (Kazune et al, 2019a ; Kazune et al, 2019b ; Dietrich et al, 2021 ). Surgical data showed that relevant intraoperative changes in organ oxygenation and perfusion quality can be identified by HSI monitoring (Jansen-Winkeln et al, 2018 ; Kohler et al, 2019 ; Thiem et al, 2021 ). Future studies should therefore examine the relationship between HSI monitoring data and the function of different organ systems during haemodynamic compromise to answer whether skin HSI indicates coherent microcirculatory impairment of multiple organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data on skin HSI monitoring in septic patients points to an association with organ dysfunction (Kazune et al, 2019a ; Kazune et al, 2019b ; Dietrich et al, 2021 ). Surgical data showed that relevant intraoperative changes in organ oxygenation and perfusion quality can be identified by HSI monitoring (Jansen-Winkeln et al, 2018 ; Kohler et al, 2019 ; Thiem et al, 2021 ). Future studies should therefore examine the relationship between HSI monitoring data and the function of different organ systems during haemodynamic compromise to answer whether skin HSI indicates coherent microcirculatory impairment of multiple organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the maxillofacial area, external electrical stimulation might be used to increase growth and proliferation of osteogenic stem cells in order to overcome xenogenous, alloplastic, allogeneic and autologous grafting procedures with their immanent limitations and risks [36][37][38][39]. Though, electrical stimulation of bone regeneration in this area has largely been unexplored and reported with inconsistent results [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a novel hyperspectral camera (TIVITA ® , Diaspective Vision GmbH, Am Salhaff, Germany), specially developed for extracorporeal perfusion diagnostics, was used as described by our group beforehand [ 17 , 18 ]. The camera system is composed of a 120 W halogen illumination source and a radiometrically calibrated 32-bit complementary metal-oxide semiconductor spectrometer, capturing images at a resolution of 480 × 640 pixels.…”
Section: Methodsmentioning
confidence: 99%